The difference of studentsâ learning outcomes between STAD model and discussion model on economics subject - Ruski, Ruski (Dinamika Pendidikan, 2016)
This research was conducted at class X SMA Negeri 1 IPS in Arosbaya. The total number of students were 140 students in order to know the difference of studentsâ learning outcomes between STAD cooperative learning model and discussion model on economics subjects. It was an experimental study using a Nonequivalent Control Group Design research design. The samples were taken by purposive random sampling technique. The samples were 69 students which were divided into the control class (X IPS3) with 35 students and the experimental class (X IPS1) with 34 students. It used post test and pre test to collect the data. Based on the results of the data analysis, it is concluded that there were differences on studentsâ learning outcomes significantly between STAD cooperative learning model (experimental class) and discussion (control class) on economics subjects. It was proven by the results of the calculation of the Z test was greater than 0.05 (4.679 > 0.05), so the hypothesis was accepted and the mean score at experimental class was higher than the control class (82.29> 74.03). Thus; the implementation of STAD method gave the good influence on studentsâ learning outcomes.Tujuan dari penelitian ini adalah untuk mengetahui perbedaan hasil belajar siswa pada mata pelajaran ekonomi menggunakan model pembelajaranÂ  kooperatif tipe STAD dengan metode diskusi biasa. Penelitian ini dilakukan pada siswa kelas X IPS di SMA Negeri 1 Arosbaya dengan jumlah siswa secara keseluruhan sebanyak 140 siswa. Jenis penelitian ini adalah penelitian eksperimen dengan menggunakan desain penelitian Nonequivalent Control Group Design. Sampel penelitian diambil dengan teknik purposive random sampling. Jumlah sampel sebanyak 69 siswa yang terbagi dalam kelas kontrol (X IPS3) dengan jumlah 35 siswa dan kelas eksperimen (X IPS1) dengan jumlah 34 siswa. Data dalam penelitian ini diperoleh melalui post tes dan pre tes. Berdasarkan hasil analisis data penelitian dapat disimpulkan bahwa terdapat perbedaan hasil belajar siswa secara siginifikan antara model pembelajaran kooperatif tipe STAD (kelas eksperimen) dengan diskusi (kelas kontrol) pada mata pelajaran ekonomi.Â  Hal tersebut dibuktikan dengan hasil perhitungan uji Z lebih besar dari pada 0,05 (4,679 > 0,05) sehingga hipotesis diterima dan perolehan rata - rata kelas eksperimen lebih tinggi dari pada kelas kontrol (82,29>74,03). Dengan demikian penerapan metode pembelajaran STAD memberikan pengaruh yang baik terhadap hasil belajar siswa.